PUBLIC PERCEPTION OF SEX BEHAVIOR PRE MARRIAGE IN AMONG ADOLESCENTS (DI DESA PULAU MUNGKUR KEC. GUNUNG TOAR KAB. KUANTAN SINGINGI) - Masrianto "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study is to provide an overview of the public perception of premarital sex behavior among adolescents and provide an overview of the factors that influence public perception . The basis of the research is a survey in the village Mungkur Island . The type of research is descriptive quantitative research is research that works with numbers further analyzed using statistics in accordance with the reality described . The collection of data through observation and interviews directly to the respondents . The sampling technique in this study using simple random sampling method ( simple random sampling ) . Sampling as many as 44 people ( 20 % ) of the 221 heads of household . The data has been collected from the results of the study were processed using frequency tables with percentages . The results showed that the majority of people perceive premarital sex behavior as a phenomenon which is common , this is because people have started to not care about the problems that occur in lingkuangannya and sika already refer to individualism . While the factors that affect the public perception that experience , customs , religion , social status , gender , education . Among the factors that most affect people's perceptions in this study is the experience and education . To minimize the occurrence rate of premarital sex behavior among adolescents , is expected to society , the elderly , would increase its role in guiding and giving guidance to the young teens that can develop into young people who have insight, smart and become the nation's next formidable.Keywords: public perception, premarital sex, juvenile